The Effectiveness of Gamification in Learning Indices and Logarithm - Ahmad, Samsiah; Hafizah Zainal Abidin, Nurul; Ahmad Kardri, Mahani; Liza Saad, Nor (International Journal of Engineering and Technology, 2018)
The use of gamification in learning has become a new approach nowadays. This approach helps the learning process to be much more fun and easy to follow. Since students may have some difficulties in understanding the mathematics concepts if they learned using the conventional approach. This paper presents a study on a game development by using the mechanics, dynamics, aesthetic (MDA) framework to study the topic of indices and logarithms. The result shows that student enjoyed the gamification approach and they are able to perform better on the topic of indices and logarithm.Â Â Â